Mobile cloud computing : foundations and service models - Huang, Dijiang; Wu, Huijun (Morgan Kaufmann, an imprint of Elsevier, 2018)
Mobile Cloud Computing: Foundations and Service Models combines cloud computing, mobile computing and wireless networking to bring new computational resources for mobile users, network operators and cloud computing providers. The book provides the latest research and development insights on mobile cloud computing, beginning with an exploration of the foundations of cloud computing, existing cloud infrastructures classifications, virtualization techniques and service models. It then examines the approaches to building cloud services using a bottom-up approach, describing data center design, cloud networking and software orchestration solutions, showing how these solutions support mobile devices and services. The book describes mobile cloud clouding concepts with a particular focus on a user-centric approach, presenting a distributed mobile cloud service model called POEM to manage mobile cloud resource and compose mobile cloud applications. It concludes with a close examination of the security and privacy issues of mobile clouds.